No Job Demand Is an Island – Interaction Effects Between Emotional Demands and Other Types of Job Demands - Geisler, Martin; Berthelsen, Hanne; Hakanen, Jari J. (Frontiers in Psychology, 2019)
Emotional demands are an inevitable feature of human services, and suggested to be a defining antecedent for workers’ stress and ill health. However, previous research indicate that emotional demands can have a favorably association to certain facets of human service workers’ motivation and well-being. Furthermore, recent research report that the effect of emotional demands on workers’ health and well-being seem to be contingent on the parallel level of other job demands. Still, initial investigations of interaction effects between emotional demands and other types of job demands have primarily focused on negative outcomes in terms of stress-related concerns and absenteeism. The present study investigated interaction effects between emotional demands and other types of job demands in relation to positive outcomes. In a larger sample of human service workers (social workers, n = 725), interaction effects were investigated between emotional demands and other job demands (quantitative demands, work pressure, and role conflict) for meaning in work and quality of work. Hypotheses stated that other job demands would moderate the relationship between emotional demands and positive outcomes, so that emotional demands would have a positive relation (i.e., act as a challenge) when the level of other demands is lower, but have a negative relation (i.e., act as a hindrance) when the level of other demands is high. Overall, the results provided support for the idea that emotional demands may act as a challenge. We found small but significant interaction effects between emotional demands and work pressure - in relation to meaning of work, as well as between emotional demands and quantitative demands, work pressure, and role-conflict, respectively - in relation to quality of work. Yet, the results did not support the assumption that emotional demands act as a hindrance when the level of other types of job demands is high. In sum, the results contribute by showing that emotional demands may promote human-service workers’ job attitudes when the level of parallel job demands is lower. We discuss the contribution of the study and the potential practical implications of the results, and give some suggestions for future research.